1997
DOI: 10.1002/pro.5560061115
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of T4 lysozyme structure by second‐site reversion of deleterious mutations

Abstract: Mutations that suppress the defects introduced into T4 lysozyme by single amino acid substitutions were isolated and characterized. Among 53 primary sites surveyed, 8 yielded second-site revertants; a total of 18 different mutants were obtained. Most of the restorative mutations exerted global effects, generally increasing lysozyme function in a number of primary mutant contexts. Six of them were more specific, suppressing only certain specific deleterious primary substitutions, or diminishing the function of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Many sites are highly tolerant of mutations with respect to one or both of expression and ACE2 binding, while other sites are highly constrained to the wildtype amino acid in SARS-CoV-2. A substantial number of sites (e.g., sites 382 to 395) are quite tolerant of mutations with respect to ACE2 binding, but are constrained with respect to expression-consistent with folding and stability being global constraints common to many sites (Fane et al, 1991;Poteete et al, 1997). There are also a handful of sites where ACE2 binding imposes strong constraints but expression does not (e.g.…”
Section: Visualization and Validation Of Sequence-to-phenotype Mapsmentioning
confidence: 99%
“…Many sites are highly tolerant of mutations with respect to one or both of expression and ACE2 binding, while other sites are highly constrained to the wildtype amino acid in SARS-CoV-2. A substantial number of sites (e.g., sites 382 to 395) are quite tolerant of mutations with respect to ACE2 binding, but are constrained with respect to expression-consistent with folding and stability being global constraints common to many sites (Fane et al, 1991;Poteete et al, 1997). There are also a handful of sites where ACE2 binding imposes strong constraints but expression does not (e.g.…”
Section: Visualization and Validation Of Sequence-to-phenotype Mapsmentioning
confidence: 99%
“…An evolutionarily important feature of mutations that interfere with protein folding is that they can frequently be compensated for by other mutations at sites distant in the three-dimensional structure (17, 18). We used a computational method (19) to predict that Arg 194 →Gly 194 (R194G), which occurs over 20 Å from H274Y in the folded structure (fig.…”
mentioning
confidence: 99%
“…Structural studies have shown that the two domains form a pocket that opens and closes to facilitate ligand binding and release (Ramanathan et al, 2011). The native structure of this protein has been determined to 1.7Å resolution by X-ray crystallography (Poteete et al, 1997). Also, T4L is notably devoid of disulphide bridges since it only has two Cys residues, located in positions 48 and 97, locations that prevent interaction.…”
Section: The Structure Of Lysozymementioning
confidence: 99%
“…That is, at least one single amino acid substitution at one of these positions results in at least a 50-fold reduction in function. Not surprisingly, the most critical amino acid residues in the protein have been found to be buried or solvent-exposed in the active site cleft (Poteete et al, 1997).…”
Section: T4 Lysozymementioning
confidence: 99%